The presence and role of arbuscular mycorrhizal fungi in coastal sand dune systems - Haller, Anjanette H. A (Rhodes University, Faculty of Science, Botany Department, 2000)
Arbuscular mycorrhizas (AM) are mutually beneficial symbiotic associations between the roots of plants and certain Zygomycetous fungi. The role of AM fungi in coastal sand dunes has been explored in many parts of the world, though little work has been conducted in South African dune systems. This study aimed to investigate the presence and extent of mycorrhizal colonisation of a coastal sand dune in South Africa. The roots of five plant species (Scaevola plumieri, Arctotheca populifolia, Ipomoea pes-caprae, Ehrharta villosa and Chrysanthemoides monilifera) were sampled along a foredune profile at Old Woman's River in the Eastern Cape. These roots were assessed for the percentage mycorrhizal colonisation they supported. Spores extracted from the rhizosphere sand of each plant species were counted and identified to genus level. Results were related to seasonality and the position of the plants along the profile. All plant species were found to be mycorrhizal. Percentage colonisation ranged from 0-92%, depending on plant species and season. Mycorrhizal colonisation was generally highest in the winter months, and especially so in I pes-caprae and E. villosa. The extent of various mycorrhizal structures in root tissue varied between plant species. Spore numbers ranged from 0-48 spores 100g-1 sand with highest numbers occurring in winter. S. plumieri and A. populifolia were associated with greatest spore abundance. Four fungal genera (Glomus, Acaulospora, Scutellospora and Gigaspora) were identified. Distribution of these genera showed seasonal variations between plant species. A bioassay, using Sorghum, was conducted to test the inoculum potentials of sand from the Scaevola hummock and the IpomoealEhrharta dune. Highest percentage colonisation occurred in plants grown in the Scaevola sand, which also had the lowest root and shoot measurements. The bioassay confirmed that AM propagules are present and viable, even in the mobile sand of the foredune. This study showed that mycorrhizal colonisation and spore numbers varied seasonally, but that the extent of this was dependent on plant species. The position of plants along the foredune profile tended to be less important than plant species. It is thought that the growth cycle and rooting system of each plant species determines seasonal cycles and abundance of AM fungi. Variation within fungal populations probably also impacts on this. Knowledge of the presence and distribution of AM fungi in this system paves the way for more detailed studies which need to examine the role of these endophytes in South African sand dunes.
Keywords: Mycorrhizas; Sand dune ecology -- South Africa; Mycorrhizal fungi